Mongolia’s “The Steppe Road” plan and China-Mongolia-Russia economic corridor - Xiwei, Du (Journal of International Studies, 2022)
In this article on China’s “Belt and Road” and Mongolia’s “Steppe Road” initiative; the establishment and realization of trilateral cooperation between China, Mongolia and Russia, or the “China-Mongolia-Russia Economic Corridor”; natural and historical factors and the main purpose of the initiative and strategy proposed by Mongolia will be presented. The next issue will touch on the way to implement China-Mongolia strategic partnership and its development prospects. Within the framework of the principle of “Three sides are one whole and move forward together” put up by the Chinese government, Mongolia proposed a specific plan for cooperation in the areas of developing Eurasian transit traffic, implementing measures to support maritime exports, developing mineral resources, creating infrastructure, and strengthening financial cooperation. In the end, the author will state about the optimalities of trilateral cooperation between China, Mongolia, and Russia. The article states the fact that the “Steppe Road” of Mongolia, originated as a concept of the natural history of mankind in the northern part is not a completely new thing for social and historical researchers, but in terms of the content of the new plan of the “Silk Road Economic Zone”. It is necessary to understand in detail that various operating conditions support the implementation of the “Belt and Road” under the abovementioned initiative such as building large-scale cooperation at the regional level, reaching consensus on implementing the cooperation, and setting the cooperation levers as well as interactions among working groups. Монгол Улсын “Талын зам” ба “Хятад-Монгол-Орос гурван улсын эдийн засгийн коридор” Хятад хэлнээс орчуулсан: Н.Ганбат Доктор (Ph.D)